Study of Demographic Pattern of Poisoning in Patients Presenting to Emergency Department of a Tertiary Care Centre, SIMS, Hapur - Gurdeep Singh1, Barakha Gupta2, Sumit Tellewar3, Vishwajeet Singh4, Abhishek Sharma1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Poisoning is a common medical emergency and one of the important cause of mortality and morbidity in developing countries like India due to easy availability of poisonous substances and its low cost. This study was carried out on poisoning cases reported to casualty of Saraswathi Institute of Medical Sciences, Hapur, UP in eighteen-months duration from 1st January 2017 to 30th June 2018. In this study, incidence was more among men (58.70%) compared to women (41.30%) and maximum cases were of age group 21 – 30 years (48.91%). More cases from rural area (89.13%) were reported and highest number of poisoning cases were admitted in the month of June 2018 (10.87%) followed by May 2017 (8.70%). Maximum cases (60.87 %) reported to casualty between 8am to 4pm. Aluminium phosphide poisoning (44.26%) constituted the highest number of cases and in maximum cases manner of poisoning was of suicidal in nature (59.78%). Majority of cases 53.26% were discharged after improvement and 3.26% cases died.